Digital waveguide models of the Panpipes - Czyżewski, A.; Jaroszuk, J.; Kostek, B. (Archives of Acoustics, 2002)
The aim of this paper is to present a digital waveguide model of the Panpipes. For the efficient modelling of the Panpipes instrument its structure and its physics were studied and discussed. Principles of the digital waveguide modelling of woodwind instruments were also briefly reviewed. In the paper two digital waveguide models of Panpipes instruments differing from each other in their complexity were presented. Consequently it enabled studying the influence of the decreasing complexity of the model on the resulting synthetic sound quality. The subjective tests performed showed that the simplifications in digital waveguide models introduced reveal no noticeable influence on the sound quality. Comparison of synthetic and real Panpipes sounds was also made and conclusions reached.